Advancing the use of gridded, online climate information for risk management in the Horn of Africa - Kipkogei, Oliver; Siebert, Asher; Jordan, Pamela; Cousin, Rémi; Jama, Abdi; Hansen, James W. (2018)
This report summarizes the discussions, deliberations and recommendations made during the side event, Advancing the use of gridded, online climate information for risk management in the Horn of Africa, to the Forty Eighth Greater Horn of Africa Climate Outlook Forum (GHACOF 48). This event was co-organized by the Climate Services for Africa project—led by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS)—and the Weather and Climate Information Services for Africa (WISER) - qEnhancing National Climate Services initiative (ENACTS), that was held on 13 February 2018 in Mombasa, Kenya. The main aim of the event was to advance shared understanding, between climate information users and providers on how the GHACOF process and member country National Meteorological and Hydrological Services (NMHSs) can support more effective use of climate information. The meeting was geared towards raising awareness on recent developments in climate information products developed for the agriculture and food security sector through the ENACTS approach and demonstrate ICPAC capabilities to support member countries in the development of gridded historical and seasonal forecast climate information Maproom products tailored to user needs. Agro-climatic variables showcased included rainfall onset dates (both in historical and forecast mode), cessation dates, historical wet and dry spells, and rainfall intensity. The meeting was also intended to bring an informed agriculture user perspective into a discussion with ICPAC and NMHSs about how the GHACOF process can be made more useful for the agriculture and food security sector. The workshop brought together representatives from member country NMHSs, experienced agricultural and food security users and champions of climate information, ICPAC, WMO, and WISER and Climate Services for Africa project partners. Workshop participants appreciated the importance of these agro-climatic variables in making timely and informed decisions.